2002
DOI: 10.1074/jbc.m203503200
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Leukocyte Protease Inhibitor Mediates Proliferation of Human Endometrial Epithelial Cells by Positive and Negative Regulation of Growth-associated Genes

Abstract: Secretory leukocyte protease inhibitor (SLPI) inhibits chymotrypsin, trypsin, elastase, and cathepsin G. This protein also exhibits proliferative effects, although little is known about the molecular mechanisms underlying this activity. We have generated SLPI-ablated epithelial sublines by stably transfecting the Ishikawa human endometrial cell line with an antisense human SLPI RNA expression vector. We demonstrate a positive correlation between cellular SLPI production and proliferation. We further show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 70 publications
6
75
1
Order By: Relevance
“…60 SLPI also exhibits proliferative effects, although its mechanism remains unknown. 61 Several studies demonstrated that SLPI is altered in cancer; it was found upregulated in ovarian and in lung carcinomas, and its serum level correlated with tumor stage and response to therapy. 62,63 The exact mechanism by which SLPI promotes malignancy is not yet known: in addition to tumor growth support, the enhancement of malignancy could be due to its effects on angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…60 SLPI also exhibits proliferative effects, although its mechanism remains unknown. 61 Several studies demonstrated that SLPI is altered in cancer; it was found upregulated in ovarian and in lung carcinomas, and its serum level correlated with tumor stage and response to therapy. 62,63 The exact mechanism by which SLPI promotes malignancy is not yet known: in addition to tumor growth support, the enhancement of malignancy could be due to its effects on angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether alterations in expression of specific uterine genes at 6.5 dpc accompany the reduced number of implantation sites noted in Bteb1 Ϫ/Ϫ mice, uteri from WT and Bteb1 Ϫ/Ϫ mice at 6.5 dpc were evaluated by QPCR for expression of progesterone-responsive, Bteb1-regulated, and/or implantation-specific genes (37,38,44,45) (Fig. 7).…”
Section: Increased Incidence Of Neonatal Lethality For Bteb1 ϫ/ϫmentioning
confidence: 99%
“…cross-linking for 90s followed by baking at 80 C for 25 min. The pre-hybridization and hybridization of membranes with 32 P-labeled human SLPI cDNA fragment (399 bp) using ULTRAhyb followed previously described protocols (Zhang et al 2002a). Membranes were washed twice in 2 SSC, 0·1% SDS and in 0·1 SSC, 0·1% SDS at 42 C for 15 min each time to remove non-specifically bound probe.…”
Section: Rna Isolation Northern Blot Analysis and Quantitative Rt-pcrmentioning
confidence: 99%
“…Over-expression of SLPI has been noted in human tumors and human carcinoma cell lines of ovarian, endometrial, respiratory tract, and neural origins (Koshikawa et al 1996, Ameshima et al 2000, Hough et al 2001, Shigemasa et al 2001, Westin et al 2002. In endometrial clonal cell lines engineered to under-express SLPI by forced expression of antisense SLPI mRNA, a direct linkage between cellular SLPI production and proliferation has been observed (Zhang et al 2002a). In these cell lines, expression of SLPI was positively correlated with increased expression of the cell cycle progression factors cyclin D1 and proliferating nuclear antigen, and was inversely correlated with expression levels of the epithelial growth inhibitors, transforming growth factor-(TGF-) and insulin-like growth factor-binding protein (IGFBP)-3, and of the tumor suppressor lysyl oxidase (Zhang et al 2002a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation